1994
DOI: 10.1103/physrevlett.72.2143
|View full text |Cite
|
Sign up to set email alerts
|

How to make large domains of disoriented chiral condensate

Abstract: Rajagopal andWilczek have proposed that relativistic nuclear collisions can generate domains in which the chiral condensate is disoriented. If sufficiently large (i.e. nucleus sized), such domains can yield measurable fluctuations in the number of neutral and charged pions. However, by numerical simulation of the zero-temperature two-flavor linear sigma model, we find that domains are essentially pion sized. Nevertheless, we show that large domains can occur if the effective mesons masses are much lighter.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
153
2

Year Published

1994
1994
2000
2000

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(165 citation statements)
references
References 16 publications
10
153
2
Order By: Relevance
“…One difficulty with getting a clean signal in this scenario is that the typical domain one expects is very small, of order 1 fm [5]. However, we would like to point out that this does not exclude the possibility of the formation of pion condensate in a large region.…”
Section: High Energy Nuclear Collisionsmentioning
confidence: 99%
See 3 more Smart Citations
“…One difficulty with getting a clean signal in this scenario is that the typical domain one expects is very small, of order 1 fm [5]. However, we would like to point out that this does not exclude the possibility of the formation of pion condensate in a large region.…”
Section: High Energy Nuclear Collisionsmentioning
confidence: 99%
“…As we mentioned in the introduction, the possibility of coherent pion emission from extended domains is very interesting and has been a subject of many investigations recently [1,2,4,5,6]. One of the problems in getting a clean signature is that such domains are expected to be very small [5].…”
Section: High Energy Nuclear Collisionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for the chiral symmetry breaking process in strong interaction the spinodal decomposition after a rapid "quench" does not yield a large correlation length [9]. Accordingly, a simulation [4] of the classical equations of motion of the linear σ-model on a 3d-lattice with spacing a = 1 fm confirmed that in the strongcoupling case no large domains form in which the π-field were essentially uniform, see also [5].We shall confirm that result but also argue that if the cutoff for the Fourier modes of the classical order parameter of chiral symmetry is pushed to larger values by some physical mechanism, e.g. parametric resonance [10][11][12], domains much bigger than the Compton wavelength of the pion can form over time-scales ≫ 1 fm.…”
mentioning
confidence: 99%